Pengaruh Kepemimpinan Supervisor HRD Dan Budaya Kerja Terhadap Kinerja Karyawan Divisi HRD Metro Indah Mall Bandung - Tiani, Ema; Syahrinullah, Syahrinullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
The purpose of this study was to determine the effect of leadership and work culture of HR managers on the performance of HRD Metro Indah Mall Bandung employees. This research is a quantitative research. The data used is primary data, namely data obtained by distributing questionnaires to the research object. The population of this study consisted of all employees of Metro Indah Mall Bandung. The sampling technique used purposive sampling with a total sample of 35 respondents. In analyzing research data using the SPSS version 26 application. The results of this study indicate that (1) leadership has a positive and significant effect on work culture; (2) Leadership has a positive and significant effect on employee performance; (3) Work culture has a positive and significant effect on employee performance; (4) Leadership has a positive and significant effect on employee performance through work culture at Metro Indah Mall Bandung.